Tradisi Menimbang Tumpeng Dalam Upacara Usabha Emping Dapat Menguatkan Sraddha Bhakti Umat Di Desa Adat Karangsari, Kabupaten Karangasem - Artana, I Kadek (Jayapangus Press, 2022)
The tradition of weighing the Tumpeng in the Usaba Emping ceremony is a community activity that fundamentally equalizes rights, duties, and responsibilities as residents of the Karangsari Customary Village, as a form of respect for their ancestors and Ida Sang Hyang Widi Wasa along with all its manifestations based on devotion, sincere and pure intentions as a silent communication medium to God. However, in implementing this tradition, there is concern and emphasis on the community, both in terms of physical/material and spiritual aspects, which already have rules or standards in the process of presenting offerings. Despite the concerns, the tradition of weighing Tumpeng continues to be practiced and preserved until now in the customs of the Karangsari Customary Village. However, it is essential to present an offering with sincere intentions and align it with one's abilities without any coercion from any party, so that the offering can yield sattwika results. This research aims to explore the process, function, meaning, and sanctions of the tradition of weighing Tumpeng, explaining why this tradition is still steadfastly followed by the community to this day. The study utilizes a qualitative descriptive research method. The findings of this research are as follows: (A) Procession of Menimbang Tumpeng in the Usabha Emping Ceremony, contains: 1). The preparation before process of creating “Tumpeng”, 2). The process of creating “Tumpeng”, 3.) The process of hand over the “Tumpeng”, 4). The process of Menimbang Tumpeng. (B). Functions and meanings in Manimbang Tumpeng Tradition in the Usabha Emping Ceremony, including: 1). The function of Manimbang Tumpeng Tradition is as a measurement of obedience to the rules that have been adopted by the community since the beginning of the Karangsari Traditional Village and serves as a medium for the formation and strengthening of character values. The character value that is formed and strengthened in this case is